TEACHER’S EXPERIENCE IN TEACHING ENGLISH LANGUAGE AT A POORLY ACCREDITED ISLAMIC SENIOR SECONDARY SCHOOL (ALIYAH MADRASA SCHOOL) IN JAMBI CITY - Tartila (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The study aims at describing an uncertified non-civil servant teacher’s experience in teaching at a lowly accredited private aliyah madrasa school. The study was phenomenology research by means of qualitative data gathering. The data in the research was obtained from individual interviews. The research participant was an uncertified non-civil servant teacher working at a poorly accredited private aliyah madrasa school in Jambi city. The data analysis was conducted following phase of Colaizzi’s technique by finding and describing themes from the participant’s statements. The results of the study showed that the teacher encounter many problems in teaching at a poorly accredited private aliyah madrasa school, such as lack of teaching resources and support from the school administrators.